Family Nursing Care Of The Family’s Process Disruption in Handling Stunting at Patrang Health Center, Jember Regency - Atika Mellenia Purvitasari Purvitasari; Tantut Susanto; Hanny Rasni; Achmad Ali Basri (Journal of Health Community Service, 2026)
Introduction: Stunting can be explained as a condition in which a child's height is less than normal based on age and sex. Families have an important role in fulfilling toddler nutrition. Disruption of the family process will lead to problems in fullfiling the nutrition of toddlers and will lead to stunting. Purpose: this case study aims to describe family nursing care for treating family process disorders in the treatment of stunting. Method: this study uses a case study approach. This case study used the family nursing care approach. The participants involved were two assisted families who experienced problems with family process disruption in the handling of stunting at Patrang Health Center. Results and discussion: after being given nursing interventions including health education related to stunting and toddler nutrition, nutrition management and PMT assistance involving the family. The result is an increase in body weight of 0.3 -0.6 kg and 1 cm in height in the two children of the assisted family. Conclusion: a good family process has an important role in fulfilling toddlers nutrient with family engagement in handling stunting.